Sosiologiese eksegese van die Ou Testament geïllustreer aan die hand van Klaagliedere 3 - Gous, I. G. P. (Verbum et ecclesia, 1993)
Sociological exegesis of the Old Testament with particular reference to Lamentations 3 People experience change as a traumatic rearrangement of their life anchors. It is possible for religion to play a positive role in the process of coming to terms with change. The book of Lamentations is representative of an attempt to interpret the loss of anchors to the people of Jerusalem in 586 B.C. We can draw from their experiences only if we come to understand their world. Sociological exegesis provides invaluable insights to this effect. The history of sociological exegesis in the study of the Old Testament is briefly sketched, followed by an overview of the book of Lamentations, with particular reference to Lamentations 3, as an example of this type of exegesis.